Transcriptomic analysis provides insight into defensive strategies in response to continuous cropping in strawberry (Fragaria × ananassa Duch.) plants - Peng Chen; He-qin Li; Xing-yue Li; Xian-hong Zhou; Xiu-xia Zhang; An-sheng Zhang; Qi-zhi Liu (BMC Plant Biology, 2022)
Abstract Background Strawberries are an important economic fruit crop world-wide. In strawberry cultivation, continuous cropping (CC) can seriously threaten yield and quality. However, our understanding of the gene expression changes in response to CC and during subsequent defense processes is limited. In this study, we analyzed the impact of CC on the transcriptome of strawberry roots using RNA-Seq technology to elucidate the effect of CC and the subsequent molecular changes. Results We found that CC significantly affects the growth of strawberry plants. The transcriptome analysis identified 136 differentially expressed genes (DEGs), including 49 up-regulated and 87 down-regulated DEGs. A Gene Ontology (GO) analysis indicated that the up-regulated DEGs were mainly assigned to defense-related GO terms, and most down-regulated DEGs were assigned to nutrient-related GO terms. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the responsive DEGs were classified in a large number of important biological pathways, such as phenylalanine metabolism, starch and sucrose metabolism, phenylpropanoid biosynthesis, glutathione metabolism and plant-pathogen interaction. We also found that four WRKY transcription factors and three peroxidase genes involved in plant defense pathways were up-regulated in the roots of strawberry plants subjected to CC. Conclusion Several unigenes involved in plant defense processes, such as CNGCs, WRKY transcription factors, PR1, and peroxidase genes with highly variable expression levels between non-CC and CC treatments may be involved in the regulation of CC in strawberry. These results indicate that strawberry roots reallocate development resources to defense mechanisms in response to CC. This study will further deepen our understanding of the fundamental regulatory mechanisms of strawberry resource reallocation in response to CC.